1993
DOI: 10.1111/j.1471-4159.1993.tb13647.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Brain Pregnenolone Synthesis by Mitochondrial Diazepam Binding Inhibitor Receptor Ligands In Vivo

Abstract: Evidence that neurosteroids are potent modulators of the action of GABA at GABAA receptors has prompted the investigation of the mechanism that controls brain neurosteroid synthesis by glial cell mitochondria in vivo. In vitro studies suggest that the interaction of the diazepam binding inhibitor (DBI)--a polypeptide that is abundant in steroidogenic cells--with glial mitochondrial DBI receptors (MDRs) is a crucial step in the physiological regulation of neurosteroid biosynthesis. MDRs bind 4'-chlorodiazepam (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 37 publications
1
54
1
Order By: Relevance
“…PK 11195 also induced signi®cant increases in both the cortical and plasma concentrations of neuroactive steroids, consistent with previous studies showing a similar e cacy of PK 11195 in stimulating steroidogenesis in brain mitochondria and in Y1 cells (McCauley et al, 1995;Zisterer & Williams, 1997). In contrast, Korneyev et al (1993) showed that PK 11195 is a speci®c blocker of PBR-mediated steroidogenesis but itself lacks steroidogenic activity. The later result may be due to the fact that in this study animals were killed 80 min after injection of PK 11195.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…PK 11195 also induced signi®cant increases in both the cortical and plasma concentrations of neuroactive steroids, consistent with previous studies showing a similar e cacy of PK 11195 in stimulating steroidogenesis in brain mitochondria and in Y1 cells (McCauley et al, 1995;Zisterer & Williams, 1997). In contrast, Korneyev et al (1993) showed that PK 11195 is a speci®c blocker of PBR-mediated steroidogenesis but itself lacks steroidogenic activity. The later result may be due to the fact that in this study animals were killed 80 min after injection of PK 11195.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, selective PBR ligands stimulate steroidogenesis in CNS and peripheral cells both in vitro and in vivo Papadopoulos et al, 1992;Romeo et al, 1992;Korneyev et al, 1993;McCauley et al, 1995). The observation that peripheral and central synthesis of neuroactive steroids can be modulated pharmacologically, together with the marked anxiolytic, anticonvulsant, sedative and hypnotic e ects elicited by i.c.v.…”
Section: Introductionmentioning
confidence: 99%
“…Neurosteroidogenesis has been first described to occur in glial cells of the central and peripheral nervous system (Compagnone and Mellon, 2000), but recently, some key enzymes have also been localized to neurons (Zwain and Yen, 1999;Follesa et al, 2000;Tsutsui et al, 2000;Patte-Mensah et al, 2003). Stimulation of PBR was shown to increase the concentration of pregnenolone, progesterone, and related steroids in brain tissue and in the plasma (Korneyev et al, 1993;Zwain and Yen, 1999;Serra et al, 2001). Here, we clearly show that stimulation of the PBR induces a modulation of synaptic GABA A R function that is independent of the activation of central benzodiazepine sites on GABA A Rs, because it persisted in the presence of flumazenil, an antagonist of the CBR.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to BZDs in the rat has been linked to subsequent altered binding to this site (Schlumpf et al, 1993) and altered mitochondrial function (Miranda et al, 1989). In adults, action at the mitochondrial BZD receptor stimulates steroid synthesis in the brain (Korneyev et al, 1993), and specific neurosteroids are potent agonists at the GABA A receptor (Rupprecht and Holsboer, 1999). Furthermore, drug action at the mitochondrial BZD receptor can affect GABA A receptor function (Costa et al, 1994).…”
Section: A Benzodiazepinesmentioning
confidence: 99%